Survei Efektivitas Pembelajaran Daring PJOK Masa Pandemi Covid-19 Terhadap Siswa Di MTs NU 06 Sunan Abinawa Pegandon Kendal - Andry Setiawan (Journal of Physical Activity and Sports (JPAS), 2021)
Corona Virus disease or commonly known as COVID-19 has made the learning system in Indonesia change drastically from conventional face-to-face learning to bold home learning. The purpose of this study was to determine the effectiveness of online learning for PJOK during the COVID-19 pandemic for students at MTs NU 06 Sunan Abinawa Kendal. This research is a quantitative descriptive study with an online survey method using google form and this study used a total population sampling consisting of 105 male and 99 female students with a total of 204 student respondents at MTs NU 06 Sunan Abinawa Kendal. After the data is collected, it will be analyzed and the percentage and the results will be described. The results showed that online learning was carried out at home, where the subject matter of PJOK using online learning 40.6% of students felt they did not understand. In the operation of online learning media 49.0% of students said they did not understand how to operate the media during online learning, then the assignment became a model often used by teachers during online learning with 69.3% in addition to online presentations of 28.6%. On the other hand 45.3% of students felt they did not understand when assignments and exams were carried out online, and 50.0% of students felt less enthusiastic when learning PJOK was carried out online so that it greatly affected student interest. Based on the results of research and discussion, it is concluded that there is a lack of effectiveness of online learning for PJOK during the COVID-19 pandemic. This is based on the results of the data that online learning as a whole was less effective in PJOK subjects during the COVID-19 pandemic at MTs NU 6 Abinawa Kendal. Keywords: Effectiveness, Student, Online Learning Abstrak Penyakit Virus Corona atau yang biasa dikenal dengan COVID-19 telah membuat sistem pembelajaran di Indonesia berubah drastis dari pembelajaran tatap muka konvensional menjadi pembelajaran rumah yang berani. Tujuan penelitian ini adalah untuk mengetahui keefektifan pembelajaran online PJOK selama pandemi COVID-19 pada siswa MTs NU 06 Sunan Abinawa Kendal. Penelitian ini merupakan penelitian deskriptif kuantitatif dengan metode survey secara online menggunakan google form dan penelitian ini menggunakan total sampling populasi yang terdiri dari 105 putra, 99 putri dengan total 204 responden siswa di MTs NU 06 Sunan Abinawa Kendal. Setelah data terkumpul akan dianalisis dan di persentase serta di deskripsikan hasilnya. Hasil penelitian menunjukkan pembelajaran daring dilakukan dirumah, dimana materi pelajaran PJOK dengan menggunakan pembelajaran daring 40,6% siswa merasa kurang mengerti. Dalam pengoperasian media pembelajaran daring  49,0% siswa mengatakan kurang mengerti dalam mengoperasikan media selama pembelajaran daring, kemudian penugasan menjadi model yang sering digunakan guru selama pembelajaran Daring dengan 69,3% selain presentasi online 28,6%. Di sisi lain 45,3% siswa merasa kurang paham ketika tugas dan ujian dilakukan secara daring, serta 50,0% siswa merasa kurang semangat ketika pembelajaran PJOK dilakukan secara daring sehingga sangat mempengaruhi minat siswa. Berdasarkan hasil penelitian dan pembahasan maka disimpulkan bahwa kurangnya efektivitas pembelajaran daring PJOK selama masa pandemi COVID-19. Hal ini berdasarkan hasil data bahwa pembelajaran daring secara keseluruhan kurang efektif dilakukan pada mata pelajaran PJOK selama masa pandemi COVID-19 di MTs NU 6 Abinawa Kendal. Kata kunci: Efektivitas, Pembelajaran, Daring Siswa